A57 ROLE OF DYNAMIC MRI DEFECOGRAPHY IN IDENTIFICATION OF PELVIC FLOOR DYSFUNCTION: A TERTIARY CENTRE EXPERIENCE. (15th March 2019) - Gill, H; Woo, M; Andrews, C N; Sawhney, S
Abstract: Background: Dynamic MRI defecography is a relatively new imaging protocol which can be extremely useful in identification of anatomic and functional pelvic floor dysfunction such as organ prolapse, anismus and fecal incontinence. Aims: The aim of the study is to assess for causes of Pelvic floor dysfunction on MRI and further characterize the findings based on functional or anatomical causes. Methods: Retrospective case series of all patients having from January 2017 to August 2018 at a tertiary care hospital (South Health Campus, Calgary, AB). After injecting rectal ultrasound gel the study was performed in resting, squeezing and defecation sequences. At least four defecation sequences were obtained to assess for complete evacuation of rectal vault. The images were then carefully reviewed to identify for descent of urinary bladder (cystocele), uterus, enterocele and rectum. The degree of prolapse was then measured and graded according to the set guidelines in radiology literature. Anismus was identified if the patient was unable to evacuate the rectal gel in four separate sequences of defecation. Results: A total of 66 patients underwent MRI Defecography. Majority of the patients referred for MRI had clinical history of constipation and to assess for compartment prolapse.The most common finding was excessive compartmental descent in 77% of patients and anismus in 38% (Table). Two patients had normal study and two patients had tumours identified as the cause for their symptoms. Most patients were referred by gastroenterologists and very few (5%) had anorectal manometry. Conclusions: Dynamic MR defecography is a novel tool for identification of both anatomic and functional pelvic floor abnormalities. The information it provides may allow for effective management (eg physiotherapy and/or biofeedback for anismus, and surgical correction for significant prolapse). Complete evaluation of the pelvis can also yield additional information such as tumors or other miscellaneous findings. However, while sensitivity appears excellent, further study is required to ascertain specificity of MR diagnosis of anismus due to patients who may have difficulty defecating due to the non-physiologic aspect of supine defecation. Given that MR scanners are much more common than anorectal manometry labs, wider adoption of MR defecography may improve diagnostic capability for pelvic floor dysfunction, which is commonly under-diagnosed. Funding Agencies: None